2018
DOI: 10.17155/omuspd.401041
|View full text |Cite
|
Sign up to set email alerts
|

Farkli Isinma Protokolleri̇ni̇n 1-Maksi̇mum Tekrar Skuat Performansi Üzeri̇ne Akut Etki̇si̇

Abstract: Bu çalışmada farklı ısınma protokollerinin 1-maksimal tekrar skuat performansına (1-MT) etkisinin belirlenmesi amaçlandı. Araştırmanın örneklem grubunu en az 3 yıl düzenli fitness sporu yapan 9 erkek (yaş: 25 ± 4,1 yıl, boy: 173,22 ± 8,46 cm, vücut ağırlığı: 75 ± 8,37 kg) oluşturdu. Katılımcılar birbirini izlemeyen günlerde 4 farklı ısınma protokolü uyguladılar. Isınma protokolleri olarak "5 dakika hafif tempo koşu (IUE)", "5 dakika hafif tempo koşu ve statik ısınma (SI)", "5 dakika hafif tempo koşu ve dinamik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…However, as would be expected at other angular velocities, a longer warm-up is also shown to have a more effective acute effect. Studies have shown that dynamic stretching exercises have a positive effect on maximal strength performance (Fujisawa et al, 2014;Kafkas et al, 2018). It has been found that the warm-up protocol with neurophysiological effects such as PNF leads to higher force production.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as would be expected at other angular velocities, a longer warm-up is also shown to have a more effective acute effect. Studies have shown that dynamic stretching exercises have a positive effect on maximal strength performance (Fujisawa et al, 2014;Kafkas et al, 2018). It has been found that the warm-up protocol with neurophysiological effects such as PNF leads to higher force production.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, it was found that the dynamic warm-up led to higher results than the other warm-up protocols. When looking at the average values, it was found that the values achieved by the dynamic warmup were the highest, followed by PNF and nally the static warm-up (Kafkas et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, PNF stretching exercises were implemented, including the Russian Twist exercise for the right and left oblique muscles, the Wide Leg Seated Stretch exercise for the adductor region, the Supine Leg Pulling towards the Chest exercise for the hamstring region, the Prone Leg Pulling towards the Buttocks exercise for the quadriceps region, and the Calf Raises exercise for the gastrocnemius region. Each movement involved a 10 s cycle of muscle relaxation and contraction, with 2 sets performed for each exercise using the contract-relaxation and hold-relaxation techniques [28]. A 30 s rest period was provided between sets.…”
Section: Proprioceptive Neuromuscular Facilitation (Pnf) Stretchingmentioning
confidence: 99%
“…Dynamic stretching exercises are thought to increase power production, unlike static stretching exercises (Harda et al, 2008). Moreover, dynamic stretching exercises can positively affect performance in parameters such as sprint and agility (Akkaya and Çolak, 2020;Kafkas et al, 2018;Polat et al, 2019). Static and dynamic stretching is one of the important strategies muscle strength and sprint performance (Rishal and Rishal, 2019).…”
Section: Introductionmentioning
confidence: 99%